1994
DOI: 10.1007/bf00181091
|View full text |Cite
|
Sign up to set email alerts
|

EMLA cream as a topical anaesthetic for ulcer debridement and simultaneous split-skin grafting

Abstract: The object of the study was to investigate the effect of EMLA cream when used as an anaesthetic for the debridement of ulcers and wounds. The cream was applied to a fresh, standardized wound caused by a dermatome, to an ulcer which was to be revised and for simultaneous split-skin grafting to both donor site and recipient area to be debrided. The effect on wound healing, the plasma concentrations of lidocaine and prilocaine and the analgesic effect following the application of EMLA to the ulcer and to both ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several trials have shown that topical EMLA is effective in reducing pain during the debridement procedure. 8,9 Sharp debridement should always be undertaken with another professional present. This assistant can reassure the patient, observe for any distress, and call for help should the need arise.…”
Section: Methods Of Debridementmentioning
confidence: 99%
“…Several trials have shown that topical EMLA is effective in reducing pain during the debridement procedure. 8,9 Sharp debridement should always be undertaken with another professional present. This assistant can reassure the patient, observe for any distress, and call for help should the need arise.…”
Section: Methods Of Debridementmentioning
confidence: 99%
“…Vanscheidt also included three open, uncontrolled studies on the use of EMLA (Wanger et al. , 1990; Barghorn & Wagner, 1994; Ohlsen et al. , 1994), and a study on lidocaine/prilocaine plasma levels after application of EMLA cream (Larsson‐Stymne, 1990).…”
Section: Pain Alleviationmentioning
confidence: 99%